ANALYSIS OF THE QUALITY OF THE HADITH AND THE VIEWS OF THE CLEARERS ON THE PROHIBITION OF MARRYING POLYSTS - Marwazi Marwazi (Journal of Islamic and Interdisciplinary Research, 2025)
This research is motivated by the increasing number of people who have interfaith marriages in Indonesia. So that it causes controversy and debate among scholars. The research method used is a literature study with a thematic approach that generally makes a reality as a starting point and then continues with the analysis process according to the perspective of the hadith. The sources of this research are primary and secondary sources. The primary source is the hadith prohibiting marrying polytheists contained in Sahih Bukhari, Thalaq book, Chapter 18. While secondary sources are in the form of books related to the theme, besides also referring to other books and writings that are relevant to this research. The research findings state that the quality of the hadith narrated by Imam Bukhari regarding the hadith prohibiting marrying polytheists in the sanad is sahih Lī Ḍzaṭih because it is narrated through narrators who are considered Ḍhabit and Tsiqah by hadith critics. As for the quality of the text of this hadith, it does not contradict the Qur'an and more authentic hadiths, so that the text of this hadith has the status of authentic Lī Ḍzaṭih and may be practiced because it has the criteria of hadith evidence. So that the hadith about the prohibition of marrying polytheists is considered relevant if it is viewed only as a warning and is considered irrelevant if the hadith is related to the prohibition of marrying polytheists against the laws in Indonesia, namely, first, the marriage of a Muslim woman with a non-Muslim man is forbidden by law. Second, a Muslim man is forbidden to marry a non-Muslim woman. Third, regarding the marriage between a Muslim man and a woman of the People of the Book, there are differences of opinion. However, after considering that the Mafsadah is greater than the maslahat, the Indonesian Ulema Council issued a fatwa that the law is forbidden.